Monitoring of Gyps species vulture in Nawalparasi district, Nepal - Subedi, P (Banko Janakari, 2009)
Critically endangered White-rumped vulture (WRV), Gyps bengalensis and Slender-billed vulture (SBV), Gyps tenuirostris monitoring was conducted in Nawalparasi district in the winter of 2005 following Postupalsky criterion. The objectives of this study were to identify and monitor nest localities, behaviour and to explore information about the vultures. A total of 48 Gyps vulture nest was located at six colonies. Of these nests, 18 were found to be active nets, six nests belonged to SBV and 12 nests belonged to WRV. Hundred percent nestling successes were observed in the study area. Restricted pesticides i.e. BHC and DDT were found used in this area. Diclofenac was the commonly used veterinary drug in the treatment of livestock. Carcasses disposal practice was found favorable to the vulture's survival. Gyps vulture richness found in this area is due to the availability of food i.e. floating carcass along the edge of the Narayani river and suitable habitat for roosting and nesting. The majority of the respondents had found favorable attitude towards vulture conservation. Further studies on Gyps vulture to identify the breeding status, head droppings behavior as well as conservation awareness program for local people and school children are recommended for long-term survival of these lords of the sky in the study area. Key words: Gyps vulture, monitoring, diclofenac, pesticides doi: 10.3126/banko.v18i2.2171 Banko Janakari, Vol. 18, No. 2, 35-43